Bhutan Economic Update, September 2017 : Hydropower Sector Clouds Macroeconomic Prospect - Ishihara, Yoichiro; Lhaden, Tenzin (World Bank, Washington, DC, 2017)
Bhutan maintained solid growth and macroeconomic stability in the first half of 2017. However, delays in hydropower construction cloud macroeconomic prospects in the coming years. Given the size and importance of hydropower projects in the economy, delays are likely to have significant negative impact on growth, revenues, and exports. Therefore, growth projections have been scaled back, although the economy is still expected to expand by 6.9 percent in 2018. Financing for development is not limited to debt financing. Maximizing access to non-debt financing such as foreign direct investment (FDI) and remittances ensures stable financing for development and less reliance on debt financing.